Changes in Economic Structure due to the Relationship between Domestic Final Demand and Production, Value Added, and Import - Bui Trinh; Nguyen Viet Phong (Current Aspects in Business, Economics and Finance Vol. 5, 2022)
Annual GDP growth averaged 7.5% between 2000 and 2006, with inflation hovering around 5%. Vietnam’s macroeconomic policy shifted to aggregated demand management from 2007 to 2012. The Keynes-Leontief relationship was used in this study to estimate the effects of some demand side factors on production, value added, and import. The study’s main findings indicated that demand-side management is no longer appropriate because the supply curve gradually approaches the horizontal axis, so any intervention on the demand side does not increase production, but only raises prices and creates a large trade deficit. This study was based on Vietnam I/O table 2000 and 2010 to analyze the change in the structure of the induced impacts for 2 periods. The 2000 I/O table represented for the 2000-2005 period and the 2010 I/O table represented for the 2006-2010 period that used 2000 as the base year. Normally, the year which compiling the input - output table should be benchmark year in order to calculate constant price, But Vietnam General Statistics Office always choose basic year arbitrary which does not based on any principles. Vietnam GSO used the year of 1994 and 2010 as basic year but only for GDP, they didn’t make for output. But they have production price index (PPI) for every year. So, that is why this research has to move the input - output table, the year of 2010 follows to price the year of 2000 (the RAS method used for balancing gross input and gross output vectors). Similar to price of basic year, the classification of input - output of years are not compatible, so we have to aggregate two I/O tables follow 15 sectors.